2020
DOI: 10.7759/cureus.8956
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis in a Patient With Coronavirus Disease 2019

Abstract: Coronavirus disease 2019 has rapidly enveloped the world in a pandemic after emerging in Wuhan, China, in December 2019. We describe a 49-year-old man presenting with fever, cough, dyspnea, and myalgia diagnosed with coronavirus disease 2019 along with rhabdomyolysis and acute kidney injury. The creatine phosphokinase was elevated to 23,800 U/L before trending down to normal levels. Rapid identification and treatment with aggressive intravenous hydration and correction of electrolyte abnormalities remain key t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 13 publications
0
27
0
4
Order By: Relevance
“…In three of these cases, with COVID-19 associated rhabdomyolysis, the patients were above 65 years of age and also developed acute kidney injury (AKI) with elevated creatinine [3,4,6]. For the other two cases, the patients were below 50 years of age, but had an associated AKI [5,7]. There was one case of a 38-year-old male with COVID-19 associated rhabdomyolysis with normal renal function, however, his peak CK was only 42,670 U/L [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In three of these cases, with COVID-19 associated rhabdomyolysis, the patients were above 65 years of age and also developed acute kidney injury (AKI) with elevated creatinine [3,4,6]. For the other two cases, the patients were below 50 years of age, but had an associated AKI [5,7]. There was one case of a 38-year-old male with COVID-19 associated rhabdomyolysis with normal renal function, however, his peak CK was only 42,670 U/L [8].…”
Section: Discussionmentioning
confidence: 99%
“…During the literature review, we found a few reported cases of COVID-19 associated rhabdomyolysis in adults [2][3][4][5][6][7][8]. In three of these cases, with COVID-19 associated rhabdomyolysis, the patients were above 65 years of age and also developed acute kidney injury (AKI) with elevated creatinine [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were male. Among the five patients, three developed AKI [20,21,24] and one of three patients received renal replacement therapy [24]. Different pathogeneses of rhabdomyolysis have been suggested; these include direct invasion of the muscle by virus, cytokine storm resulting in muscle damage, and muscle injury by circulating viral toxins [23].…”
Section: Discussionmentioning
confidence: 99%
“…We are seven months into the COVID-19 pandemic, and the full neuromuscular manifestation has yet to be understood. Rhabdomyolysis from COVID-19 infection has been described [ 1 - 4 ] but is largely non-fatal. Most reported creatinine kinase (CK) levels are only mildly elevated - less than five digits.…”
Section: Introductionmentioning
confidence: 99%